The Social Contract in the MENA Region and the Energy Sector Reforms - Sara Brzuszkiewicz (Fondazione Eni Enrico Mattei (FEEM), 2017)
During the last few years and because of the low oil prices in particular, the increasing awareness of the unsustainability of subsidized systems led several MENA countries to take steps to lower subsidies, which have been part of the social contract for decades, especially as far as the energy sector is concerned. Nowadays, the need for reforms is compelling for more than one reason. Namely, the subsidized system distorts market trends, fosters inefficient use of resources, depresses foreign direct investment and fuels overconsumption, which is no longer sustainable, particularly as far as the population growth in most of the MENA countries is concerned. In this paper both the resource-abundant countries and the energy importing nations will be analyzed, in order to investigate similarities and differences between the two and to carry out an initial assessment of the reforms in two representative countries, namely Saudi Arabia, exporting country par excellence, and Egypt, which imports energy.
Keywords: O1; O13; 330; Energy Sector; Subsidies; Subsidy Reforms; MENA Region; Saudi Arabia; Egypt; Rentier State; Resource Curse Theories